The east London geriatric in situ simulation (ELGIS) programme: implementing in situ simulation in elderly care in two district general hospitals. (2019) - Walker, Grace; Dormandy, Letitia; Quah, Corrine; Sullivan, Rebecca; Dasgupta, Deblina
No abstract available